Assembly of 1T′-MoS2 based fibers for flexible energy storage. Issue 11 (11th March 2020) - Pan, Hui; Lin, Jingyi; Han, Xiaoyu; Li, Yao; Meng, Xin; Luo, Ruichun; Broughton, Joseph James; Imtiaz, Muhammad; Chen, Zhixin; Wang, Dawei; Zhu, Shenmin; Liu, Pan; et al.
Abstract : The hydrothermal synthesis of well-soluble 1T′-MoS2 sheets and the assembly of 1T′-MoS2 /graphene oxide fibers from liquid crystals endow excellent electrochemical properties. Abstract : As a new type of 2D material, 1T′-MoS2 has become one of the fastest growing topics, owing to its extraordinary electrical conductivity and electrochemical activity. Nevertheless, these marvelous properties have not yet been realized in their macroscopic structures such as films and fibers, due to the lack of an assembly method. Herein, we report the synthesis of well-soluble 1T′-MoS2 sheets, which can form a nematic liquid crystalline structure in their aqueous suspensions. The liquid crystalline suspensions were then assembled into macroscopic 1T′-MoS2 fibers via a simple and cost-effective dry-spinning process. A similar process can be used for the preparation of 1T′-MoS2 /graphene oxide (1T′-MoS2 /GO) fibers from 1T′-MoS2 /GO 2D/2D composite liquid crystals. The fabricated 1T′-MoS2 /GO fibers exhibited an excellent electrical conductivity of 1.5 × 10 4 S m −1 as well as a high tensile strength of 145 MPa. When used as an electrode, the fibers showed an extremely high capacitance of 1379.8 F cm −3 (∼645 F g −1 ) at a scan rate of 10 mV s −1 by using K3 [Fe(CN)6 ]/K4 [Fe(CN)6 ] as the electrolyte. Our findings will open up an avenue for liquid crystal physics of low dimensional non-carbon materials beyond graphene, and stimulate a wide range of application explorations, especially on energy storage.